1998
DOI: 10.1038/sj.bmt.1701238
|View full text |Cite
|
Sign up to set email alerts
|

Influence of protective isolation on outcome of allogeneic bone marrow transplantation for leukemia

Abstract: Summary:Various isolation strategies are used to prevent infections during bone marrow transplantation; data on their efficacy are lacking. We studied whether use of high efficiency particulate air filtration ( and increases survival after allogeneic bone marrow transplants for leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 26 publications
(28 reference statements)
0
73
0
Order By: Relevance
“…24 A study from the International Bone Marrow Transplant Registry showed higher survival rates in patients cared for with stricter isolation procedures in LAF rooms than those not treated in LAF rooms in the hospital. 25 However, in another prospective randomised trial, patients treated in LAF rooms had a significantly lower incidence of bacteraemia, but the same survival rates as those treated in conventional single rooms. 7 These studies only included hospitalised patients, but in hospitals many patients are treated for infections, which give rise to antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…24 A study from the International Bone Marrow Transplant Registry showed higher survival rates in patients cared for with stricter isolation procedures in LAF rooms than those not treated in LAF rooms in the hospital. 25 However, in another prospective randomised trial, patients treated in LAF rooms had a significantly lower incidence of bacteraemia, but the same survival rates as those treated in conventional single rooms. 7 These studies only included hospitalised patients, but in hospitals many patients are treated for infections, which give rise to antibiotic-resistant bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although more recent publications have alluded to the potential detrimental effects of nosocomial infections in hospital settings when the OP program was established in 1995, there was strong support for the use of environmental infection control measures to minimize infections in HSCT recipients. [22][23][24][25] The literature suggested the use of laminar air flow units, patient isolation units, prophylactic antibiotics, anti-microbial contamination and low-microbial diets improved survival among patients. Despite this trend, our OP program was established without the use of any of these environmental controls.…”
Section: Discussionmentioning
confidence: 99%
“…1,10,[16][17][18] With focus on neutropenia, strict isolation in sterile units or laminar airflow compartments has been standard care practice for many years. [19][20][21] Improvement in diagnosing infections, availability of better broad spectrum antibiotics, novel antifungal and antiviral agents, introduction of intravenous immunoglobulins and vaccination strategies have changed attitudes. Infections are considered as treatable conditions.…”
mentioning
confidence: 99%